Proton aurora and relativistic electron microbursts scattered by electromagnetic ion cyclotron waves - Shumko, Mykhaylo; Gallardo-Lacourt, Bea; Halford, Alexa Jean; Blum, Lauren W.; Liang, Jun; Miyoshi, Yoshizumi; Hosokawa, Keisuke; Donovan, Eric; Mann, Ian R.; Murphy, Kyle; Spanswick, Emma L.; Blake, J. Bernard; et al. (Frontiers in Astronomy and Space Sciences, 2022)
Charged particle precipitation from Earth's magnetosphere results in stunning displays of the aurora and energy transfer into the atmosphere. Some of this precipitation is caused by wave-particle interactions. In this study, we present an example of a wave-particle interaction between Electromagnetic Ion Cyclotron waves, and magnetospheric protons and electrons. This interaction resulted in a co-located isolated proton aurora and relativistic electron microbursts. While isolated proton aurora is widely believed to be caused by Electromagnetic Ion Cyclotron waves, this unique observation suggests that these waves can also scatter relativistic electron microbursts. Theoretically, nonlinear interactions between Electromagnetic Ion Cyclotron waves and electrons are necessary to produce the intense sub-second microburst precipitation. Lastly, detailed analysis of the auroral emissions suggests that no chorus waves were present during the event. This is in contrast to the most commonly associated driver of microbursts, whistler mode chorus waves, and supports other less commonly considered driving mechanisms.